DAMPAK PERUSAHAAN BATUBARA TERHADAP LINGKUNGAN DAN EKONOMI LOKAL MASYARAKAT SEKITAR KECAMATAN PADANG BATUNG DAN KECAMATAN SUNGAI RAYA KABUPATEN HULU SUNGAI SELATAN, KALIMANTAN SELATAN - M. Army Chairuddin; Idiannor Mahyudin; Luthfi Fatah; Yusuf Aziz (Universitas Lambung Mangkurat, 2023)
Coal mining activities are long-term activities, involve high technology and are capital intensive. Mining activities cause potential changes in the income of people who work as rubber farmers due to damage to the landscape and land conversion that affect rubber production. The research aims to analyze the impact of coal companies on the environment and the local economy of the people around Padang Batung sub-district and Sungai Raya sub-district, Hulu Sungai Selatan district, South Kalimantan. This research was conducted in Hulu Sungai Selatan District, Padang Batung District and Sungai Raya District which included 3 villages namely Malutu Village, Ida Manggala Village and Batang Kulur Kiri Village. Analysis of the impact of coal mining is carried out on 2 parameters, namely environmental and economic parameters. The environmental components that are of concern to the community at the study site are air quality degradation (increased dust), river water pollution, increased noise, emissions from heavy equipment and transport exhaust gases and waste water. Coal mining activities in the Padang Batung District and Sungai Raya District are able to have a positive economic impact on local communities with a multiplier effect value of 1.01 in 2021. The direct economic impact of coal mining activities is Rp. 4,336,921,464, indirect economic impact of Rp. 1,132,608,000 and the economic impact is Rp. 714,468,000.